Memanfaatkan Digital Marketing bagi Usaha Rumahan Sayuran Hidroponik dengan E-Commerce sebagai Media Promosi - Sarwindah, Sarwindah; Laurentinus, Laurentinus; Rizan, Okkita; Hamidah, Hamidah (LPPM STT Terpadu Nurul Fikri, 2021)
This research aims to take advantage of marketing strategies with digital marketing using e-commerce as a promotional medium where currently the cultivation of vegetables and fruit developed in the world of agribusiness makes farmers compete with each other and cultivate in the agricultural sector, one of which is the hydroponic planting method. Therefore, automatically the selling power of the vegetables itself also has a competitive edge. The difficulty and the added lack of promotional and sales media at Hydroponic Gardens is the background for making information systems on Hydroponic Gardens, so that by utilizing digital marketing it can increase promotional media and increase sales results. The research method used is FAST while the application program was developed using PHP and the database used was MySQL and the script was developed with Sublime Text. The purpose of this research is to utilize e-communication and build a system in order to facilitate promotion and sales as well as make it easier for owners to be able to view transactions and sales reports. So that the management of all existing data can be monitored through the system with an easier process.